Research of Superimposed Carburizing Heat Treatment Process for Aviation Gear Material 16Cr3NiWMoVNbE - Rongchun Qiu; Kui Chen; Yi Wen; Junqiong Huang (Jixie chuandong)
Carburizing and quenching heat treatment process is the key to improve the surface quality of mechanical parts. In order to improve the surface quality of the planetary gear made of 16Cr3NiWMoVNbE， after analysis， take the carburizing after high temperature tempering， quenching after cold treatment process， so that the surface hardness of the product reach above 60 HRC after carburizing quenching. In the process of uncontrollable layer depth of secondary superimposed carburizing， the process control method of slope rise and temperature drop is adopted in the temperature stage above Ac3， the depth of carburizing layer is controlled accurately. Finally， the process test is carried out to verify it. Thus， the superimposed carburizing heat treatment process with different carburizing layer depth between the tooth surface of planetary gear and the surface of inner hole is developed. The excellent comprehensive performance of 16Cr3NiWMoVNbE aviation gear material is obtained make full use of.